The Relationship Between Permissive Parenting and the Nutritional Status of Toddlers in the Mergangsan Health Center Working Area - Christy, Christy; Bartini, Istri; Utami, Riadini Wahyu; Amelia, Sylvi Wafda Nur (CV. Rayyan Dwi Bharata, 2024)
Background: Malnutrition is one of the main problems in toddlers. Nutrition Surveillance in 2021, found that toddlers with very underweight were 1.2% and underweight were 6.1%. SSGI in 2021 stated that the percentage of stunted (very short and short) was 24.4%. Factors that affect children's nutritional status include diet and parenting, which also affect nutritional status. Objective: The purpose of this study was to analyze the relationship between permissive parenting and nutritional status. Methods: This type of research uses analytical observational methods, using a cross sectional approach conducted in the work area of the Mergangsan Health Center. sampling technique using purposive sampling, namely 95 respondents, from a total population of 1798. Data were analyzed using the spearman statistical test. Results: Non-permissive parenting is 39 (75%) children with normal nutritional status and 13 (52%) children whose nutritional status is not normal. Respondents who applied permissive parenting were 26 (78.8%) children with normal nutritional status and 7 (21.2%) children with abnormal nutritional status. The Spearman test results obtained a P value of 0.8820.05, this means that H0 is accepted and Ha is rejected. Conclusion: There is no relationship between parenting patterns and the nutritional status of toddlers aged 0-59 months in the Mergangsan Health Center Working Area.